Board members' contribution to strategy: The mediating role of board internal processes - Carmen Barroso-Castro; Maria Mar Villegas-Peri\~nan; Marta Dominguez (European Research on Management and Business Economics (ERMBE), 2017)
This study aims to explore what directors do on the board, to what extent the processes occurring in the board allow the sharing and integrating of the existing knowledge, thus facilitating the board members' contributions to strategy. We adopt the view that the internal board processes increase the impact of the cognitive resources on board performance. Using survey data from 200 large Spanish companies we demonstrate that directors' level of knowledge of the firm and board job-related diversity positively influence the degree of the board's strategic involvement. Additionally, the internal processes that take place within the board – particularly Cognitive Conflict, the Critical and Independent Approach and the Comprehensive Discussion Process – influence the board's strategic involvement and play a partial mediating role on the aforementioned relationships. However, our results show no evidence for a positive relationship between Board Meeting Dynamics and the board's strategic involvement.
Keywords: M10; 650; Corporate governance; Internal board processes; Board strategic involvement; Board diversity; Board knowledge of the firm; Mediation analysis